PROFITABILITY AND TECHNICAL EFFICIENCY OF CUCUMBER PRODUCTION AMONG SMALLHOLDER FARMERS IN OYO STATE, NIGERIA - adeoye, iyabo; Balogun, Lawrence Olubunmi (Journal of Agricultural Sciences (Belgrade), 2016)
Cucumber is one of the most important exotic vegetables in Nigeria. Its profile is increasing due to wide spread knowledge of its inherent health benefits. To sustain availability of the crop in order to meet increasing demand, there is the need to enhance its productivity. Crop productivity depends on efficient use of both material and human resources utilized in the production process. This study therefore examined profitability and efficiency of cucumber production in Iseyin local government area of Oyo state. Primary data on socioeconomic characteristics of farmers, input and output quantity and prices were collected from 73 cucumber farmers and analyzed using descriptive statistics, budgetary technique and stochastic frontier. Majority of the farmers were male (96.7%) with average age of 46.4 years. An average of 17.1 years of farming experience cut across both gender groups. The average hectare was 1.5 with average yield of 5,368kg/ha. Budgetary analysis revealed that Net profit of ₦239,440/ha, Profit margin percentage of 55.8% and returns on every naira invested of 1.26 was obtained.  This is an indication that cucumber production is profitable in the study area. The result of the stochastic frontier indicated that significant factors affecting cucumber production include farm size and volume of agrochemical used. Socioeconomic factors indicated to have effects on cucumber productivity were age, education status of farmers and access to credit. Mean technical efficiency of production was 0.68.  The study recommends capacity building for farmers on appropriate combination of resources.